AMBUSH MARKETING: THE KULULA.COM PERSPECTIVE (The Pretoria Student Law Review, 2021)
Ambush Marketing is often described as a type of ‘parasitic marketing.’ However, before we look into ambush marketing one has to consider the essence of marketing and more specifically, advertising. The purpose of advertising is essentially to create brand awareness, by somehow making the public aware of the product you offer as a company or firm. Sponsorship is a mechanism through which brand awareness can be created. Sponsorship can be defined as a commercial arrangement, whereby a sponsor pays a certain sum of money (a sponsorship fee) or provides certain products, services or other facilities to the sponsored party, in return for which, the sponsor is granted certain rights of association with the sponsored party.1 What better way to create awareness than at a major global event? By paying the event organisers an agreed amount, they associate your product with their event. For instance, First National Bank (FNB) agree to sell the Fédération Internationale de Football Association (FIFA) world cup tickets at their branches across the country without sharing in any of the profits, they may not be generating any money from actual ticket sales but they get thousands of people coming in and out of their branches daily, thus more importantly, creating band awareness. Sponsors should be protected by organisers from unofficial non-sponsors, but to what extent? While the law should attempt to safeguard the investments of sponsors of events, we should not be unreasonable in our attempts. Laws and regulations should be applied with at least a modicum of sanity and those responsible for their enforcement should avoid adopting a dictatorial approach.
Keywords: Ambush Marketing; sponsorship; unofficial non-sponsors; investments; laws and regulations